Green Ca-source of cockle shells converted to calcium acetate for environmental sustainability - Somkiat Seesanong; Chaowared Seangarun; Banjong Boonchom; Natee Ohpasee; Nongnuch Laohavisuti; Wimonmat Boonmee; Pesak Rungrojchaipon (My University, 2024)
This work aimed to synthesize and characterize the calcium acetate monohydrate (Ca(CH3COO)2·H2O) from the exothermic reaction between CaCO3 powder derived from cockle shells with three different acetic acids (8, 10, and 12 mol L−1) concentrations by the rapid and easy process without pH and temperature control to lead to cheap chemical production. The physicochemical characteristics of all synthesized Ca(CH3COO)2·H2O samples are investigated based on the chemical compositions, crystal structures, vibrational characteristics, morphologies, and thermal behavior to confirm the target compound. A suitable concentration of 10 mol L−1 CH3COOH was chosen to produce Ca(CH3COO)2·H2O with the highest yield (96.30 %), maximum calcium content (96.2 % CaO) with lower impurities, and time consumption of 17 h. The calcium acetate product obtained from cockle shells in this work shows differences in thermal stability, morphological structure purity, %yield, and metal contamination with those reported obtained from other sources and another shell type in the previous work. This research investigates the transformation of cockle shell waste into CaCO3 for the production of calcium acetate, aiming to address environmental sustainability concerns by reducing the use of calcium ore resources and greenhouse gas emissions.
Keywords: Cockle; biodegradable polymer synthesis and properties